Historic urban fabrics and urban expansion: A typo-morphological analysis of the regional capitals in southern Peru - Mamani Cabrera, Yoseline (2025)
The cities of southern Peru can be understood as urban organisms shaped by the superimposition of historical, social, and territorial layers. This article offers a comparative analysis of the urban structure of Cusco, Arequipa, and Tacna through the typomorphological framework proposed by Gianfranco Caniggia and Gian Luigi Maffei, aiming to identify common patterns in their formative processes. The study applies a qualitative-comparative methodology based on the multiscalar typological process of anthropic space. Results indicate that the urban structure of these cities is influenced by territorial structuring elements, the functions of initial settlements, typical fabrics, and characteristic buildings. Specifically, Cusco presents a longitudinal structure, Arequipa an organic one, and Tacna a border-form structure. The research concludes that typomorphology is a key tool to interpret urban complexity and to guide planning strategies in Latin American contexts, linking historical memory with future urban projects.